Tolerance of four Malaysian chlorophytes to nitrate and ammonium pollution - Siew-Theng, Foo,; Loy Chu, Wan-; Siew-Moi, Phang, (Malaysian Journal of Science, 2001)
Microalgae tolerant to high levels of NaNO3, and NH4Cl have the potential for use in bioremediation of nitrogen-rich agro-industrial wastewaters and as bioindicators for nitrogen enrichment in tropical freshwater environments. Four indigenous chlorophytes from Malaysia, namely Chlorella vulgaris UMACC 001, Scenedcsmus quadricauda UMACC 039. S. quadricauda UMACC 041 and Ankistradesmus convolutus UMACC 101 were grown at NaNO3 and NH4,Cl levels ranging from 2.9(control), 50, 75, 120, 170 to 250 mM. The control contained the level of nitrogenous compound found in Bold’s Basal Medium. Of the four chlorophytes, C. vulgaris UMACC 001 was most tolerant to NaNO3 and NH4Cl as the cell number and final biomass were much higher when grown at increased levels (> 2.9 mM) of these nitrogen sources. In contrast, S. quadricauda UMACC 041 and A. convolutus UMACC 001 were sensitive to high levels of NaNO3 and NH4Cl as indicated by the very low cell number at levels above 75 mM as compared to the control. Within the range of NaNO4 levels tested, the four chlorophytes grew best at 50 mM. For the range of NH4Cl levels tested, C. vulgaris UMACC 001 grew best at 75 mM whereas the other chlorophytes grew best at 50 mM. Based on the growth responses to the varying levels of nitrogen, C. vulgaris UMACC 001 may be a potential species for treatment of agro-industrial wastewaters and as bioindicator for nitrogen pollution.